Evolução Pedogenética em Duas Vertentes do Maciço de Baturité - CE. - Barbosa, Wesley Rocha (2008)
Given the importance of the climate conditions for the development of soils, together with the occurrence of moisture and temperature variations in very near areas, The purpose of this work was to identify and characterize the soils into a sequence in the moist and dry slopes of Maciço de Baturité, which is considered a moist enclave inserted in the semi-arid region of Ceará State. It was analyzed eight profiles, 04 out of them in each slope, from the morphological description, physical, chemical and micromorphological attributes on necessaries for the understanding of the main pedogenetic processes acting. It was identified the following soil classes: Haplic Cambisoil (P1 and P4) and Yellow Argisoil (P3 and P4) in the moist slope and Red Argisoil (P1), Chronis Luvisoil (P2) and Haplic Cambisoil (P3 and P4) in the dry slope. The moist side showed characteristics of a large potential of water percolation that caused greater loses of bases by lixiviation and high contents of exchangeable A1, whose values were S = 2,2 cmolc.kg¹ and Al = 4,1 cmolc.kg¹ and, consequently, strongly acid reaction (middle pH = 5,1). The dry slope showed a characteristic of an environment favorable for oxidation caused by greater aeration of the pedoenvironment, denounced by the reddish color. Comparing the moist slope’s data with the dry slope’s, the smallest thickness of the solum of the dry slope’s pedons, as well as, lower concentration of clay in the horizons B (306 to 343 g.kg¹) and high contents of exchangeable cations (S = 12,8 cmolc.kg¹), besides other physical, chemical and morphological attributes, indicate the lower degree of evolution of soils in the dry slope, confirming the contrast among the soils located in opposite sides of Maciço.